68Ga-DOTATATE PET/CT Uptake in Prostate With an Incidental Finding of Prostatic Acinar Adenocarcinoma and Metastatic Neuroendocrine Cancer to the Liver. (August 2021) - Nisar, Muhammad Umer; Costa, Daniel N.; Jia, Liwei; Öz, Orhan K.; de Blanche, Lorraine
Abstract : Abstract: A 69-year-old man with history of metastatic neuroendocrine tumor presented for initial staging with 68 Ga-DOTATE PET/CT. 68 Ga-DOTATATE PET/CT showed incidental focal increased DOTATATE uptake in the left apical prostate tissue, which was thought to be of benign etiology. Digital rectal examination later was consistent with a palpable nodule along with elevated prostate-specific antigen of 7.0 ng/mL. MRI of prostate demonstrated a 3.8-cm lesion followed by a targeted biopsy that revealed prostatic acinar adenocarcinoma. Chronic inflammatory cell infiltrates were also noted on biopsy, and this may have been the cause of increased DOTATATE uptake seen on 68 Ga-DOTATATE PET/CT study.